The Potential Of Internationalization Of Small And Medium Micro Enterprises In SAWO Leather Crafts, Magetan District, East Java, Indonesia - Hari Purwanto (International Journal of Science, Technology & Management, 2021)
The Magetan leather handicraft business is one of the long-established and surviving SMEs and contributes to the creation of employment and income for the community. Currently, the marketing of leather handicraft products is still limited to meeting local and national needs so that limited market demand makes leather handicraft difficult to develop. Globalization and increasingly advanced information technology have become opportunities for the Magetanleathercraft industry to penetrate the international market, however, various obstacles arise considering that penetrating the global market is not easy for small businesses that have many limitations. The purpose of this case study is to examine the opportunities and obstacles of the Magetan leather handicraft business to penetrate the international market. This research approach is qualitative with case studies.owner of leather handicraft, owner of leathercraft marketing shop, the buyer of leathercraft, an employee of leathercraft. Data analysis includes (1) data collection (2) data display (3) data reduction and (4) conclusions.[1]The results showed that there were obstacles to the internationalization of the Magetan leather handicraft business, namely complicated international trade procedures for SMEs, No marketing channels abroad for SMEs, Limited SME resources. The solution that can be offered from this problem is not to let SMEs directly penetrate the global market independently given the limitations they have, but by providing a mediator that can bridge SMEs with foreign consumers with a Marketplace, Exporters, or Cooperatives.